2017
DOI: 10.3389/fped.2017.00131
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Bronchospasm and Allergy

Abstract: Sport is an essential part of childhood, with precious and acknowledged positive health effects but the impact of exercise-induced bronchoconstriction (EIB) significantly reduces participation in physical activity. It is important to recognize EIB, differentiating EIB with or without asthma if the transient narrowing of the airways after exercise is associated with asthmatic symptoms or not, in the way to select the most appropriate treatment among the many treatment options available today. Therapy is prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 64 publications
0
21
0
3
Order By: Relevance
“…The logistic regression was performed using both crude models and models adjusted for possible confounders (age, gender, BMI, socioeconomic variables (parent's educational level, unemployment and disability of parents, living with adoptive parents), dietary variables that were associated with serum PFASs concentrations in TFF1 (18), physical activity at leisure time, smoking and chewed tobacco use). The covariates for the regression models were selected based on the results of the previously published studies (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and were reported to be associated with risk of asthma and/or with PFASs exposure, therefore being possible confounders. The ANOVA linear trend tests were performed to evaluate if there were significant linear trends.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The logistic regression was performed using both crude models and models adjusted for possible confounders (age, gender, BMI, socioeconomic variables (parent's educational level, unemployment and disability of parents, living with adoptive parents), dietary variables that were associated with serum PFASs concentrations in TFF1 (18), physical activity at leisure time, smoking and chewed tobacco use). The covariates for the regression models were selected based on the results of the previously published studies (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and were reported to be associated with risk of asthma and/or with PFASs exposure, therefore being possible confounders. The ANOVA linear trend tests were performed to evaluate if there were significant linear trends.…”
Section: Statistical Analysesmentioning
confidence: 99%
“… 13 Other indirect bronchoprovocation tests include the hypertonic saline challenge and the mannitol test. 61 The latter was developed to improve the availability and standardisation of osmotic challenge testing; 62 , 63 however, the sensitivity and specificity of the mannitol challenge has yet to be well established. 11 , 13 …”
Section: Diagnosismentioning
confidence: 99%
“…En los próximos pasos, que también se consideran como medicamentos complementarios, por lo general, además de ICS para mejorar los síntomas y la función pulmonar, por un aumento en la actividad antiinflamatoria. Pueden considerarse especialmente para algunos pacientes que experimentaron efectos secundarios utilizando ICS en niños menores de 5 años, y son efectos especialmente en el asma inducida por el ejercicio (Caggiano, Cutrera, Di Marco, & A., 2017) Las opciones de tratamiento en el Trámite 3 difiere dependiendo del grupo de edad. En niños pequeños, una dosis media de ICS además de SABA es la solución preferida, mientras que, en los adolescentes, así como en los adultos, la combinación de dosis baja de ICS / LABA (BDP / formoterol o budesonida / formoterol) como tratamiento de mantenimiento con SABA como agente de alivio, o dosis bajas de ICS / LABA (BDP / formoterol) como tanto el mantenimiento y el tratamiento calmante puede ser considerado.…”
Section: Antagonistas De Los Receptores De Leucotrienos (Ltras)unclassified